My art has a secret mission: the role of the arts in Australian rural, remote and Indigenous communities - Anwar McHenry, Julia (Common Ground Publishing, 2009)
Images of Australia are dominated by rural landscapes and depictions of the outback. However, rural Australia is undergoing social and economic change, with some commentators suggesting that rural Australia is in crisis. Rural Australia, in general, ranks lower than the rest of Australia on health and other socio-economic indicators. This is especially true for the nation's Indigenous population for whom the majority live outside the metropolitan areas of the capital cities. It has been suggested by policy makers, the arts sector, and communities themselves that the arts can address some of these inequities. Yet, there is limited research on the role of the arts in the health and sustainability of rural communities. This research examines the role of the arts in the rural communities of the Mid West region of Western Australia, a socially and economically diverse region, traditionally reliant on primary industry, with a high proportion of Indigenous residents. The findings show that people engage in the arts for a wide variety of reasons in an even wider variety of settings. More importantly, despite initial intentions of an arts project or activity, the arts provides common ground and a means to develop, strengthen, or reinvent a sense of community in response to local and global challenges.